A 21.6 kDa tegumental protein of Clonorchis sinensis induces a Th1/Th2 mixed immune response in mice. Issue 4 (9th October 2018) - Chung, EunJoo; Kim, Yu Jung; Lee, Myoung‐Ro; Cho, Shin‐Hyeong; Ju, Jung‐Won
Abstract: Introduction: Clonorchis sinensis is a major parasite affecting the Korea population. Despite the high infection rate and pathogenicity, very few studies have been conducted to investigate the immune responses against the proteins of C. sinensis . Methods: In this study, in vitro immune response induced by a recombinant 21.6 kDa tegumental protein derived from C. sinensis (rCsTegu21.6) was confirmed in murine dendritic cells and T cells. For the in vivo analysis, each mouse was immunized three times. Total serum IgG and T cell cytokine production were determined by ELISA, while T cell proliferation was detected by a WST (Water‐Soluble Tetrazolium salt)‐1 assay. Results: In vitro tests indicated that rCsTegu21.6 treatment increased the expression of surface molecules, such as CD40 (77%), CD80 (52%) and CD86 (46%), on murine dendritic cells and the secretion of cytokines (TNF‐α, IL‐6, IL‐1β, IL‐10, and IL‐12p70). Moreover, co‐culturing dendritic cells activated by rCsTegu21.6 with allogenic T cells induced T cell proliferation over time. rCsTegu21.6 also stimulated specific antibody production and cytokine secretion [IL‐2, IL‐4, and interferon (IFN)‐γ)] from T cells following immunization in vivo. Notably, rCsTegu21.6 predominantly induced IgG1 production and secretion of the Th2 cytokine IL‐4, regardless of the type of adjuvant used. Conclusion: These results serve as a foundation for the development of tegumental protein‐based vaccines against C. sinensis . Abstract : The liver fluke Clonorchis sinensis is a well‐known fish‐borne trematode that can survive in the bile ducts and cause various diseases. In this study, we characterized a 21.6 kDa tegumental protein and evaluated its immunological potential for further vaccine development.